An Analysis of Oral Reading Miscues for the English language and Retelling Comprehension of Fifth Preparatory Graders in Thiqar, Iraq : Psycholinguistic Study - Ali, Dr. Asaad Abderada; Ghnee, Ass.Lecture Mohammed Rashid (Thi Qar Arts Journal, 2023)
This study is an attempt to identify and analyze the oral reading miscues (30) students,(15 males and 15 females) are chosen randomly from fifth Preparatory graders in Thiqar. The teachers choose the students as being remedial readers and those who are identified as being exceptionally good readers are excluded from the population of the study for the purpose of having a sample very much of average readers.The reading miscues inventory which is first developed by Goodman, is used to code and analyze in depth the students' miscues with respect to how these miscues relate to their counterparts in the text. They are classified under graphic, sound, syntactic and semantic categories. This analysis also shows the effect of these miscues on the students' comprehension: meaning and grammatical acceptability.The study shows the high percentage of correction attempts made by the male readers. This high percentage of correction attempts shows that the fifteen females' readers are successful in their oral reading.The results of this study also reveal that the females' readers are syntactically and semantically acceptable. The results also show that the readers are strong comprehenders while the male readers' miscues are not syntactically and semantically acceptable. Thus, this study applies the psycho-linguistic reading process, which is illustrated by comparing unexpected and predicted reading-related responses. An extensive analysis of the phenomenon of oral reading is possible with the help of this taxonomy of reading errors and signals. This taxonomy is developed in close proximity to the theory and has been improved by use in an ongoing series of thorough studies on oral reading.